PENERAPAN MODEL PEMBELAJARAN TREFFINGER UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF SISWA KELAS X SMA NEGERI 9 PEKANBARU PADA MATERI USAHA DAN ENERGI - Azis, Hasbi; Zulhelmi, Zulhelmi; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to improvement of creative thingking ability in the subject of physics by applying Treffinger learning model. This research was conducted at Senior High School 9 Pekanbaru in February to May 2018. Research subjects in this study are class of X MIA 4 grade two academic year 2017/2018. Research subject were chosen by using sampling purposive technique. The design of this study is One Group Pretest-Posttest Design. Instrument of data collection in this research is a test of creative thinking ability which consists of 10 items essay by using descriptive analysis. From the descriptive analysis, the average achieves 78.13 is good category. In accordance with the average absorption that has been obtained, then the effectiveness of learning is in the effective category. To increase students creative thinking ability of 0.56 which is in the medium category. The result of this study can be concluded that the learning of physics in the class X MIA 4 Senior High School 9 Pekanbaru by applying Treffinger learning model can improve students creative thinking ability on work and energy concept which have achieved the success of three indicators from four indicator creative thinking ability provided, that is indicators of fluency, flexibility thinking and elaboration thinking.Keywords: Creative Thinking, Treffinger Learning Model